The Influence of Work Culture, Work Discipline, and Motivation on Employee Performance - Ida Abdul Gofar; Nurlinda (Kusuma Negara Business School, 2021)
The purpose of this study was to determine the effect of work culture, work discipline, and motivation on employee performance at PT. DHL Supplychain Indonesia. The population and samples used in this study amounted to 70 respondents. The data collection method used a questionnaire distributed through google form. Hypothesis testing in this study using SPSS analysis tools by conducting validity tests, reliability tests, classical assumption tests, multiple linear regression, coefficient of determination (R²) test, f test, and T test. The results of the study explain that work culture has an effect on employee performance, work discipline affects employee performance, and work motivation does not affect employee performance.